Analisis Penyebab Rendahnya Kreativitas dan Motivasi Belajar Matematika Kelas IV pada Materi FPB dan KPK - Rabela, Shania Wini; Imansyah, Farizal; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Mathematics Class IV in the firstsemester of elementary school contains SK 2 material. Understanding and using factors and multiples in problem solving. KD 24 Solve problems related to the KPK and FPB. The KPK and FPB materials are materials that students must understand.Because thismaterial will continue to the class above. The purpose of this study is to find out and describe the causes of low creativity and motivation in learning mathematics for FPB and KPK materials in fourth grade students of SD Negeri 70 Palembang. The researchmethod used in this study is a qualitative descriptive method. The results showed that the factors causing the low creativity and motivation to learn mathematics in FPB and KPK materials in fourth grade students at SD Negeri 70 Palembang were the low ability of students, unsupportive student environmental conditions and the distance learning system that caused a lack of direct guidance from the teacher or teacher math.